Ultralong hydroxyapatite microtubes: solvothermal synthesis and application in drug loading and sustained drug release. Issue 14 (23rd March 2017) - Zhang, Yong-Gang; Zhu, Ying-Jie; Chen, Feng; Sun, Tuan-Wei; Jiang, Ying-Ying
Abstract : One-step solvothermal synthesis of monodisperse, single-crystalline, ultralong hydroxyapatite microtubes is reported. Abstract : In this work, monodisperse single-crystalline ultralong hydroxyapatite (HAP) microtubes have been successfully synthesized using a reaction system containing CaCl2, NaOH, (NaPO3 )6, oleic acid, water and ethanol by a solvothermal method. The formation mechanism of HAP microtubes and the effects of solvothermal temperature, pH value, Ca/P molar ratio, and volume ratio of solvents on the product have been investigated. Due to the unique tubular structure, the as-prepared ultralong HAP microtubes exhibit high biocompatibility and superior properties in drug loading and sustained drug release. The as-prepared HAP microtubes are promising for applications in various biomedical fields such as drug/gene delivery and bone defect repair.